IDENTIFICATION OF CHILDREN WITH MOTOR COORDINATION DIFFICULTIES: APPLICATION OF THE CHECKLIST (Fiep Bulletin - online, 2014)
Introduction: Developmental Coordination Disorder (DCD) is characterized as a huge difficulty in movement coordination, usually permanent, not related to physical, neurological and/or mental problems.  The diagnose is obtained from the Movement ABC (Movement Assessment Battery for Children, M-ABC, Henderson & Sugden, 1992),  a standardized battery that consisted of eight items in three categories: manual dexterity, ball skills, and balance.  A check-list is used by teachers in order to provide assessment of the nature and incidence of movement difficulties by children.  Taking in consideration the results of the test of motor competence from the M-ABC, the objective of this study was to verify, in our educational context, the ability of teachers from elementary school  to identify children with motor difficulties through the check-list.  Method: Participants were 198 students between 7 and 8 years of a public elementary school and  the 13 classroom teachers. Children were assessed through the check-list by theirs classroom teachers and through the motor competence test M-ABC by the researchers and university students, duly trained.  Results. A low correlation between the results obtained by the teachers in the check-list and the results obtained in the M-ABC,  r = .17, p > 0.01. Teachers were able to correctly identify 41,9% of the children with high (DCD) and low (at risk) motor difficulties. Conclusion: The results pointed out that classroom teachers have difficulty identifying children with severe (DCD) or moderate (at risk) motor difficulties.  Therefore, this identification must be complemented by the motor component of the M-ABC.  A question raised from these results is weather physical education teachers when available and working in the shool setting would be able to identify correctly children with DCD and/or at risk using the check-list.
Keywords: assessment; motor coordination; children